The role of social media in changing community social behaviour: Study case Wahhabi conflict in East Lombok - Latifah, Latifah; Fahrisa, Titing Reza (Jurnal Sosiologi Dialektika, 2023)
Sentiment between religious groups (Wahhabis and non-Wahhabis) due to misuse of social media has sparked open conflict between these groups. This paper aims to explain the case of the burning of the mosque of the Wahhabi in As-Sunnah Foundation by the ‘Sunni Muslim' group in Aikmel, East Lombok, by looking at the contribution of digital media to changes in people's behavior patterns and the impact it has on human security especially community and individual security. The discussion focuses on answering the question: how the media contributes to changes in social behavior that's threats to human security in the case of the burning of the Wahhabi As-Sunnah group mosque in East Lombok. This study uses a qualitative-descriptive method with media strategies and human security as the analytical framework. Data collection was carried out using in-depth interviews, observation, focused group discussion, and literature review. This study shows that digitalization contributes to changes in people's behavior. Social media (Facebook and YouTube) are used to spread disinformation and hate speech between religious groups in East Lombok which trigger conflict. The open conflict became a threat to the security of the Wahhabi community and individuals in East Lombok.